Análise acústica de clusters com tap na fala de crianças com e sem desvio fonológico - Silva, Pedro Henrique Sousa da (2018)
The purpose of this dissertation is to explain/describe acoustic patterns of tap in complex onset in the speech production of children with and without phonological disorder with respect to Acoustic Phonetics. It also aims to investigate certain phonetic details of clusters with tap, such as those involving voiced and voiceless stops, and the voiceless labiodental fricative, which precede the onset reported tap with respect to the Brazilian Portuguese phonological system. The guiding question for this research is: to what extent do acoustic productions of tap in complex onset differ in the oral production of children with and without a phonological disorder? The methodological procedure consisted of the application of a figure naming test to elicit disyllabic target words with tap on complex onset followed by the tonic vowel [a]. Tests were applied to two distinct groups of participants: one group consisting of children with a phonological disorder (N = 4) and the other consisting of children with no phonological disorder (N = 4). Data were recorded with a model H4n Zoom Recorder (Handy Recorder), with a sample rate of 44100 Hz, and a lapel microphone. All participants' data were recorded in an acoustically treated booth. The basic hypothesis was that the acoustic productions of tap in complex onset of the group of children with a phonological disorder (GDF) are significantly different from those in the group of children without the disorder (GSDF). The tap was analyzed from the waveform and a spectrographic analysis. As for the specific hypotheses, it was stated that GDF and GSDF are distinguished as: (i) voiceless stops, the acoustic parameter being the relative VOT; (ii) voiced stops, the parameters being the VOT, voicing/(un)voicing; (iii) the voiceless labiodental fricative, the parameters being the relative duration of the voiceless fricative, and the spectral composition. The results corroborated the basic hypothesis. Regarding the first specific hypothesis, it was found that there are differences in GDF and GSDF productions, but they are not significant. However, considering the effects of sex on the VOT, a significant difference (p = 0.03571) was found in relation to the mean VOT values of velar [k], with the mean of girls being higher than that of boys. As for the other hypotheses, no significant differences were found.